2011
DOI: 10.1002/qua.22556
|View full text |Cite
|
Sign up to set email alerts
|

Toward understanding the protein oxidation processes: OH addition on tyrosine, phenylalanine, or methionine?

Abstract: Oxidation of peptides and proteins by OH radicals produced in oxidative stress or in radiotherapy, accidental irradiations, etc., is well known to form oxidative metabolites that are responsible for numerous diseases including neurodegenerative pathologies. Tyrosine (Tyr), Phenylalanine (Phe), and Methionine (Met) residues are known to be the major targets of OH radicals. This study aims at better understanding the OH addition process on these three amino acids. On the basis of different amino acid prototypes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…This step could explain the nature of transients as well as the final compounds, but was too fast to be observed by pulse radiolysis. Several computational papers dealt with the oxidation of methionine and tyrosine [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…This step could explain the nature of transients as well as the final compounds, but was too fast to be observed by pulse radiolysis. Several computational papers dealt with the oxidation of methionine and tyrosine [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Details on the performance of our modified Bruker Esquire 3000+ were already published [14]. Different electron energies were used (40)(41)(42)(43)(44) We used the relatively small basis set 6-31G(d) (SB) and the greater basis set 6-311+G(2d,2p) (GB) considering the experimental and the theoretical difficulties linked to measurements of redox potentials.…”
Section: Ms Operationsmentioning
confidence: 99%
“…We had previously performed preliminary theoretical approaches of the oxidation competition between Tyr and Met in isolated peptide models [43]. These first thermodynamic data indicated that Tyr •+ was more stable than Met •+ .…”
Section: What About Intramolecular Electron Transfer Involving Methiomentioning
confidence: 99%
“…Sci. Technol., 3(2): 106-116 August 2014 doi: 10.13170/AIJST.0302.06 111 considered (Laloo and Mahanti, 1990;Giulivi and Davies, 2001;Malika et al, 2010;Faller et al, 2002;Foppoli et al, 1997;Trouillas et al, 2011). Amino acids with aromatic side chain were oxidized more rapidly than the alkyl side chain amino acids.…”
Section: Charge Distributionmentioning
confidence: 99%